Peace without reconciliation: post-conflict as a permanent condition - Šljuka, Aleksandar (Political Life, 2026)
This paper presents a review of Stefan Surlić’s monograph The Balkans After the War: Peacebuilding or Statebuilding?, which examines the nature and sustainability of post-conflict orders in the Western Balkans. Starting from the premise that post-conflict is not a transitional phase but a permanent condition of political life, the author develops a theoretical framework that moves beyond dominant liberal-institutionalist approaches. The analysis shifts the focus from institutional design to the question of political legitimacy, emphasizing the gap between procedural and consensual legitimacy as a key source of long-term instability.Through a comparative analysis of Bosnia and Herzegovina, North Macedonia, and Kosovo, the paper demonstrates that consociational institutional arrangements simultaneously contribute to stability while reproducing ethnic divisions, thereby limiting the prospects for deeper political integration. A key contribution of the book is the conceptualization of vertical integration as a relationship of trust between citizens and institutions, whose absence represents a central challenge for post-conflict societies. Furthermore, the role of international actors in sustaining hybrid forms of sovereignty is highlighted, alongside the structural incentives shaping the behavior of political elites. The paper concludes that the limitations of contemporary peacebuilding models are not merely the result of inconsistent implementation, but stem from the very logic of post-conflict orders themselves. This opens space for further research on the conditions under which a political community can be perceived as legitimate by all its members.